2018
DOI: 10.1021/acsomega.8b02298
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted aza-Friedel–Crafts Arylation of N-Acyliminium Ions: Expedient Access to 4-Aryl 3,4-Dihydroquinazolinones

Abstract: A one-pot microwave-assisted aza -Friedel–Crafts arylation of N -acyliminium ions, generated in situ from o -formyl carbamates and different amines, is reported. This metal-free protocol provides rapid access to diverse 4-aryl 3,4-dihydroquinazolinones in excellent yield without any aqueous workup. A solvent-directed process for the selective aza -Friedel–Crafts arylation of electron-rich aryl/heteroaryl/butenyl-tethere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Sawant and co-workers reported in 2018 an efficient and a rapid way giving access to 4-aryl 3,4-dihydroquinazolines using a microwave-assisted aza-FC reaction in the presence of acetic acid (AcOH). 33 A one-pot cascade sequence was explored starting with the generation of cyclic N -acyliminium ions, from O -formyl carbamates 10 and ammonium acetate (Scheme 3). The in situ generated ion 11 could then react with indole 12 using microwaves, thanks to an aza-FC reaction.…”
Section: Achiral Aza Friedel–crafts Reactionsmentioning
confidence: 99%
“…Sawant and co-workers reported in 2018 an efficient and a rapid way giving access to 4-aryl 3,4-dihydroquinazolines using a microwave-assisted aza-FC reaction in the presence of acetic acid (AcOH). 33 A one-pot cascade sequence was explored starting with the generation of cyclic N -acyliminium ions, from O -formyl carbamates 10 and ammonium acetate (Scheme 3). The in situ generated ion 11 could then react with indole 12 using microwaves, thanks to an aza-FC reaction.…”
Section: Achiral Aza Friedel–crafts Reactionsmentioning
confidence: 99%
“… 46 Although the aromatic ketones have tremendous applications, yet conventional strategies to produce such ketones often suffer from major challenges of complicated synthetic procedures and environmental concerns. 47 , 48 The use of homogeneous catalysts, for example, protic acids, 49 soluble metal halides, 50 and substituted anhydrides 51 in stoichiometric amounts and other homogeneous catalysts, for example, Ln(OTf) 3 -LiClO 4 , 52 LiClO 4 -acyl anhydride complex, 53 (PhCN) 2 PtCl 2 /AgSbF 6 , 54 Re-Br(CO) 5 , 55 and so on in the catalytic amount spectacle certain progress in the reaction. However, the industrial application of these homogeneous catalysts is also associated with various shortcomings because of the noneconomical reaction process and environmental issues.…”
Section: Introductionmentioning
confidence: 99%
“…Again, the Friedel–Crafts (FC) acylation of aromatic substrates with acid halides is a fundamental and important conversion in organic synthesis. In particular, regioselective FC acylation to synthesize aromatic ketones have potential significance in chemical industry as the ketones are involved in the preparation of various synthetic intermediates, chemical feedstocks, pharmaceuticals, and fine chemicals . Although the aromatic ketones have tremendous applications, yet conventional strategies to produce such ketones often suffer from major challenges of complicated synthetic procedures and environmental concerns. , The use of homogeneous catalysts, for example, protic acids, soluble metal halides, and substituted anhydrides in stoichiometric amounts and other homogeneous catalysts, for example, Ln­(OTf) 3 -LiClO 4 , LiClO 4 -acyl anhydride complex, (PhCN) 2 PtCl 2 /AgSbF 6 , Re-Br­(CO) 5 , and so on in the catalytic amount spectacle certain progress in the reaction. However, the industrial application of these homogeneous catalysts is also associated with various shortcomings because of the noneconomical reaction process and environmental issues. , Therefore, design and development of a highly reactive and economical catalyst system with less environmental disputes is quiet challenging.…”
Section: Introductionmentioning
confidence: 99%
“…26 This is a simple, highly attractive approach for accessing novel and densely substituted DHQ analogues, based on an array of different chemistries (Scheme 1). [27][28][29][30][31] During the course of our investigations on the reactivity of Nacyliminium ions (I), we observed the formation of an unknown side-product (4a) when formic acid was used as a solvent, in an aza-Henry based cyclization cascade, in lieu of acetic acid (Scheme 1). Subsequent characterization studies revealed that this compound retained the DHQ core but lacked the expected C4-substituent.…”
Section: Introductionmentioning
confidence: 99%